Leading by example: Do the biggest and most generous donors influence others to give more health aid?. Issue 1 (12th January 2015) - Beech, Amy; Kwak, Do Won; Tang, Kam Ki
Abstract : Purpose: – The purpose of this paper is to explore the interdependence between donor countries' health aid expenditures. The specific form of interdependence considered is the leader effect, whereby an influential country has a positive leverage effect on other donor countries' aid expenditure. The opposite case of a free-rider effect, whereby a single donor country has a negative leverage effect on its peers, is also considered. Design/methodology/approach: – Focusing on the identification of the leader effect avoids the estimation bias present in the identification of the peer group effect, due to endogenous social effect. The empirical analysis focuses on Development Assistance for Health provided by 20 OECD countries over the period of 1990-2009. Aid commitment and aid disbursement are distinguished. Findings: – When aid dynamics, country heterogeneity, and endogeneity are accounted for, there is no evidence that the biggest donor – the USA, or the most generous donors – Norway and Sweden, exhibit any leverage effects on other donor countries' aid expenditures. Originality/value: – This is the first paper to examine the leader and free-rider effects in health aid provision as previous studies focus on peer effects. Any evidence of leader or free-rider effects (or the lack of it) adds to the understanding of international political economy especially in the area of foreign aid provision.